I Am What Is a Photograph: Photofiction as Performative Autoethnography. (April 2019) - Stephens, Tim
This article is based on one fact about the author's biography and one retold memory of the author's mother. Each relates to the conception of the author. It takes the form of a performative autoethnography employing photofiction. 1 The article specifically interrogates the grounded nature of subject identity in bodily experience, as matter, and chronology through speculative inquiry and the intersubjective relation, as themselves "photographic, " mediated through language. However, notions of subject and experience, photograph and academic language are pushed to an extreme position until highly reflexive and to a point beyond literary metafiction. The article thus elaborates and enacts photofiction as autoethnography, replacing "meta" thinking and representational thinking about events and memories, with the nonrepresentational, to write the real [self] as nondualistic: experiential data as nonphotography. The onto-epistemological position of the researcher, author, Subject, in relation to his or her own status is in fact a photofiction.